Molecular cloning and characterization of leucine aminopeptidase from Fasciola gigantica - Narin Changklungmoa (2018)
M17 leucine aminopeptidase (LAP) is one of a family of metalloexopeptidases, of which short peptide fragments are cleaved from the N-terminals. In this study, the full length of cDNA encoding Fasciola gigantica LAP (FgLAP) was cloned from adult parasites. The amino acid sequences of FgLAP showed a high degree of identity (98%) with that from Fasciola hepatica and a low degree of identities (11% and 9%) with those from cattle and human. Phylogenetic analysis revealed that the FgLAP was closely related and grouped with F. hepatica LAP (FhLAP). Northern analysis showed that FgLAP transcriptional products have 1800 base pairs. Analysis by RNA in situ hybridization indicated that LAP gene was expressed in the cecal epithelial cells of adult parasites. A polyclonal antibody to a recombinant FgLAP (rFgLAP) detected the native LAP protein in various developmental stages of the parasite. In a functional test, this rFgLAP displayed aminolytic activity using a fluorogenic Leu-MCA substrate, and was significantly inhibited by bestatin. Its maximum activity was at pH 8.0 and enhanced by Mn 2+ ions. Localization of LAP proteins by immunohistochemistry and immunofluorescence techniques indicated that the enzyme was distributed in the apical cytoplasm of cecal epithelial cells. Because of its important metabolic role and fairly exposed position, FgLAP is a potential drug target and a possible vaccine candidate against fasciolosis. © 2012 Elsevier Inc.